Relação família-escola: o estado da arte na pós-graduação brasileira - Andreza Maria de Lima; Laêda Bezerra Machado (EccoS – Revista Científica)
The family-school relationship has occupied more space in scientific production in Brazil. In this article, we analyze summaries of Brazilian theses and dissertations on the family-school relationship produced in the period 2004-2013. We reconstruct the history of this relationship in Brazil from authors such as Cunha (2003) and Faria Filho (2000). The study, of a qualitative nature, is of the State of Art type. For the location of the works, we consulted three databases: the thesis bank and dissertations on the family-school relationship of the Observatory Family-School Sociology of the Federal University of Minas Gerais (OSFE / UFMG); the database of the Postgraduate Program in Family and Contemporary Society of the Catholic University of Salvador (UCSal); and the thesis and dissertation bank of the Coordination for the Improvement of Higher Education Personnel (CAPES). The localized s (112) were mapped in relation to objectives, theoretical references, methodological options (empirical field, participants, collection and analysis procedures) and results. For analysis, we used the Thematic Categorical Content Analysis Technique, resulting in the construction of three categories: family-school relationship and family educational strategies; Family-school relationship and socio-school phenomena and Family-school relationship: phenomena and / or aspects of this relationship. Regarding the theoretical references, less than half of the s mentioned the authors who supported the studies. With regard to the methodological path and the results of the research, much information was also absent. Nevertheless, we have found some research that points to a certain resistance of teachers with different family configurations from the traditional one and the influence of this resistance in the relation with the family and / or the teaching work; and others that deconstruct the widespread view that the families of public school students are disorganized. Finally, we point out the need for further research on the subject, as there are still several aspects to be explored; as well as the importance of the s being carefully prepared by the researchers.